Wayang Sukuraga : Pendidikan Karakter melalui Kearifan Lokal di Sekolah Dasar - Sugiri, Atot (Elementary Teacher Education Program, Majalengka University, 2023)
This research is to analyze the character values ​​of the local wisdom of Wayang Sukuraga in Sukabumi City towards character education in elementary schools. This study uses a qualitative approach with a qualitative descriptive method which aims to describe the value of character education in local wisdom in Wayang Sukuraga. This research stems from the researcher's interest in examining more deeply the connection between the phenomena experienced by the informants. The informants of this study were an artist from the city of Sukabumi and a teacher who uses the wayang Sukuraga media in learning. Data collection was carried out using interview techniques, observation, and documentation studies. Data analysis in this study included collecting data, reducing data, presenting data, and drawing conclusions. The results of this study are that the Sukuraga puppet has values ​​in the formation of human character because the Sukuraga puppet story is taken from stories of everyday life. This shows that the formation of character contained in wayang sukuraga can be implemented by elementary school students in their daily lives. So that the character education obtained in this Sukuraga puppet is so that humans can stay away from evil and do good.